Brain glucose uptake during transcranial direct current stimulation measured with functional [18F]FDG-PET - Christoph Kraus; Andreas Hahn; Helen Sigurdardottir; Benjamin Spurny; Wolfgang Wadsak; Markus Mitterhauser; Marcus Hacker; Siegfried Kasper; Rupert Lanzenberger (Brain Imaging and Behavior, 2020)
Previous evidence indicates that transcranial direct stimulation (tDCS) is a neuromodulatory brain stimulation technique. Easy applicability, low side-effects and negligible costs facilitated its wide–spread application in efforts to modulate brain function, however neuronal mechanisms of tDCS are insufficiently understood. Hence, we investigated the immediate impact of tDCS on the brain’s glucose consumption in a continuous infusion protocol with the radioligand 2-[ 18 F]fluoro-2-deoxy-D-glucose ([ 18 F]FDG) and positron emission tomography (PET). This novel functional PET (fPET) method is capable to reliably detect area-specific and dynamic absolute glucose demand related to neuronal activity in a single molecular imaging session. Fifteen healthy subjects underwent tDCS at 0.5, 1 and 2 mA (mA) at the bilateral dorsolateral prefrontal cortex (dlPFC, cathodal right) for 10 min during functional [ 18 F]FDG-PET lasting 70 min. Active stimulation compared to sham did not yield significant changes in glucose consumption at any tested stimulation intensity in this paradigm. Exploratory investigation of aftereffects provided hints for increased glucose consumption with a delay of 5 min at 1 mA in the right posterior temporal cortex. This is the first study investigating changes of glucose consumption in the brain during tDCS. The lack of immediately increased glucose consumption indicates that energy demanding processes in the brain such as glutamatergic signaling might not be immediately increased by tDCS. However, our results implicate the need of fPET investigations for medium-term and long-term effects.

Towards Improved Pharmacokinetic Models for the Analysis of Transporter-Mediated Hepatic Disposition of Drug Molecules with Positron Emission Tomography - Irene Hernández Lozano; Rudolf Karch; Martin Bauer; Matthias Blaickner; Akihiro Matsuda; Beatrix Wulkersdorfer; Marcus Hacker; Markus Zeitlinger; Oliver Langer (The AAPS Journal, 2019)

Task-relevant brain networks identified with simultaneous PET/MR imaging of metabolism and connectivity - Andreas Hahn; Gregor Gryglewski; Lukas Nics; Lucas Rischka; Sebastian Ganger; Helen Sigurdardottir; Chrysoula Vraka; Leo Silberbauer; Thomas Vanicek; Alexander Kautzky; Wolfgang Wadsak; Markus Mitterhauser; et al. (Brain Structure and Function, 2017)